Hochgebirge von Semien - Äthipoien: Zwei Karten zur Dynamik der Höhenstufung von der letzten Kaltzeit bis zur Gegenwart - Hurni, Hans (ERDKUNDE, 1981)
In the first map (supp. Ill), the last cold period glacial and periglacial forms and limits are shown in a scheme and a detailed survey throughout the whole of Simen (cf. Fig. 1). The orographic snowline, reconstructed by the moraines of the glacial belt, varies very much with slope aspect, being up to 300 m lower in northern facing catchments. Widespread periglacial slope rubble deposits with depths up to 15 m, are mapped to scale if deeper than 2 m. Their lower limit with depths of 0.1 m can be detected in soil profiles only. Parts of this limit, which were not investigated in the field, are reconstructed according to the topographical correlations of the mapped parts with altitude, slope aspect, length, and gradient. The periglacial belt in Simen enclosed 470 sq km, and the glacial belt 30 sqkm, with 13 sqkm covered by ice. Formation processes and related climatic conditions can be used to date the last cold period. The climate being 7°C cooler and poor in rainfall and run-off, correlates with a climatic period in Ethiopia between about 20000 and 12 000 BP (Late Wurm, cf.H.Hurni,1981). No map is given for the Holocene period. However, it is possible to distinguish three morphological main processes. A first process is the intensive natural erosion period immediately after the last cold period, before vegetation regrowth took place in the periglacial belt. A second process is the pedodynamic period of soil formation and deposition of volcanic ash in a long and stable period. A third process finally, is the increasing human interference with soil erosion on the cultivated fields below about 3700 m, during the last two millenia (cf. Abb. 2). In the second map (supp. IV), present day altitudinal belts are shown in a scheme and survey of the Simen mountains. Resulting correlations of the mapped geobotanical limits (cf. Fig. 3) with altitude, slope aspect and gradient, can be interpreted ecologically with own climatic data (eg. Fig. 4). The frost detrital, or lower periglacial limit lies at approx imately the altitude of 180 days of frost change per year. The Erica timber line correlates with a mean annual temperature of 7.7°C, and the Hagenia-Juniperus-Olea tree limit with 8-10°C, whereas the Acacia trees are limited in southern facing aspects at 3100 m by frost, and in northern facing aspects at 2400 m by the here intensified rainfall and clouding, and the reduced radiation. An interesting coincidence can be observed between the Erica timber line and the climatic barly limit, whereas the upper limit of grains and pulses' cultivations proceeds parallel to the Acacia limit, about 300 m higher up. A treatening ecological catastrophe with irreversible damage to nature and agriculture, is the conclusion drawn from the study of the dynamics of altitudinal belts with regard to human interference (cf.H. Hurni and B. Messerli,1981).